Pushing the Natural Frontier Progress on the Integration of Biomaterial Cues toward Combinatorial Biofabrication and Tissue Engineering - Guimarães, Carlos F (Advanced materials (Deerfield Beach, Fla.), 2022)
© 2022 Wiley-VCH GmbH.